Application of a compound containing silica for removing ammonium in aqueous media. Issue 1 (24th March 2014) - Darvishi Cheshmeh Soltani, R.; Safari, M.; Rezaee, A.; Godini, H.
<x xml:space="preserve">Abstract</x> In the present investigation, removal of ammonium from aqueous solutions by a compound containing silica was considered. The compound was a waste of ferrosilicon compound produced during Ferro‐alloy manufacturing. The results showed that an increase in the pH of solution up to 7 caused a rapid increase in the adsorbed ammonium to 36.21 mg/g. But adsorbed ammonium was decreased to 26.51 mg/g as the initial pH reached to 10. The amount of adsorbed ammonium was increased with contact time and initial ammonium concentration. A contact time of 180 min was selected because there was no significant increment in adsorbed ammonium as contact time was further increased. The results exhibited suitability of the pseudo‐second order kinetic model (R2 = 0.9867). Increasing initial ammonium concentration from 10 to 180 mg/L resulted in an increment in adsorbed ammonium from 6.69 to 59.13 mg/g, respectively. The obtained data were fitted to Langmuir, Freundlich, and Dubinin–Radushkevich (D‐R) isotherm models in which the obtained correlation coefficient showed the relatively better fitness of the data to Langmuir model (R2 = 0.9969) with a maximum adsorption capacity of 78.74 mg/g. © 2014 American Institute of Chemical Engineers Environ Prog, 34: 105–111, 2015